Dampak Kebijakan Dividen, Tingkat Bunga, dan Inflasi terhadap Harga Saham Perusahaan Sektor Keuangan di Yogyakarta - Rosmiati Rosmiati; Isnaini Khoirunnisa; Henike Sobolim; Bangun Putra Prasetya (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
This study aims to analyze the impact of dividend policy, interest rates, and inflation on the stock prices of financial sector companies in Yogyakarta. The data used are secondary data obtained from company financial reports and macroeconomic indicators over a specific period. The analytical method employed is multiple linear regression to determine the extent to which the independent variables affect stock prices as the dependent variable. The results indicate that dividend policy has a significant positive effect on stock prices, while interest rates and inflation have a negative impact. These findings provide important implications for investors and financial managers in formulating investment strategies and dividend policies, as well as in considering macroeconomic conditions in financial decision-making within the financial sector.